Independent predictors of bleeding complications in patients undergoing PCI with concomitant treatment with bivalirudin in clinical practice results from the improver registry - Koeth, Oliver; Gulba, Dietrich; Huber, Kurt; Madsen, Jan Kyst; Darius, Harald; Schneider, Steffen; Zeymer, Uwe (Journal of cardiovascular pharmacology, 2013)
Bleeding complications are associated with an adverse outcome after a percutaneous coronary intervention (PCI) is performed. Traditional risk factors for bleeding complications are age, gender, underweight, hypertension, and renal impairment. The aim of our study was to identify the independent predictors of bleeding complications in patients undergoing a PCI with concomitant treatment with bivalirudin. - Methods: - Between January 2005 and June 2006, a total of 3799 patients, undergoing a planned or urgent PCI with concomitant bivalirudin treatment, were prospectively enrolled in the ImproveR registry. One hundred two centers out of 12 European countries participated in the ImproveR registry. In this analysis, we report the incidence of bleeding complications in subgroups to be at a high risk for developing bleeding complications. A multivariate logistic regression model was performed to identify the independent predictors of bleeding complications. - Results: - Major bleeding complications occurred in 1.7% of the patients. The highest incidence of major bleeding complications was observed in the subgroup with a sheath size ≥7F (4.3%), heparin use after the PCI (3.5%), and additional use of GP IIb/IIIa inhibitors (3.3%). The multivariate regression analysis revealed female gender [odds ratio (OR), 2.3; 95% confidence interval (CI), 1.4-3.8], heparin after the PCI (OR, 3.1; 95% CI, 1.9-5.1), and sheath size ≥7F (OR, 3.1; 95% CI, 1.8-5.4) as the independent predictors of bleeding. - Conclusions: - The rate of occurrence of bleeding complications in patients undergoing a PCI with concomitant use of bivalirudin is low in clinical practice. Female gender and procedural factors, such as sheath size and heparin after PCI, were associated with an increase in bleeding complications, whereas other traditional risk factors associated with bleeding, such as age, diabetes mellitus, and renal impairment, had no impact.
Gesehen am 08.12.2021